The Artistic Function of Affectionate-diminutive Word Forms in the Dramatic Poem Advocate Martian by Lesya Ukrainka (Linguostylistic Studies, 2021)
The article considers semantic loading and functionality of affectionate-diminutive word forms in Lesya Ukrainka’s dramatic poem Advocate Martian. The study findings argue that the use of diminutives in the poem is multifunctional. They serve as a means of characterizing the chronotope, individual characters and their relationships, contributing to the structural perfection of the work.The main character of the drama Martian is controversial by his nature. This feature and importance of the sacrifices he made to fulfill his mission as a defender of Christian prisoners require a closer study of his personal life, his family relationships, and the lexical-stylistic means by which they are conveyed. Diminutives are lexical means of the denotation of the feelings of kindness, care, affection, intimate cordiality that prevail in this family. The choice of different lexical-semantic forms by various speakers is determined by their individual characteristics, the situation in which the dialogue takes place or the change of emotional states during the conversation.The comparison of the draft and the final version of the work allow tracing the evolution of the creative idea. The study has revealed that modeling of the character of Martian as well as other characters, portraying of their relationships strongly depend on the frequency of the affectionate-diminutive word forms usage.On the other hand, this comparative analysis has also identified that in the course of writing her dramatic poem, the poetess rejected the use of a significant number of diminutives that allowed adjusting the ideological content to the work. The removal of some affectionate and diminutive word forms is motivated by the fact that their redundancy was at odds with the strong, stable, rational, and holistic image of the main character. The contradiction between the reproduction of the Roman reality of the third century and the reception potential of the Ukrainian reader has been eliminated by the dosed and motivated choice of affectionate and diminutive word forms.
Keywords: appellation; draft manuscript; final autograph; functionality